Entrepreneurial management, entrepreneurial orientation and Turkish small firm growth - GÜRBÜZ, FATMA GÜLRUH; ERGUN, HANDE SİNEM (My University, 2009)
Purpose: The purpose of this paper is to investigate the relationship between entrepreneurial orientation (EO) and entrepreneurial management (EM) and their impact on small firm growth. EO is regarded as the strategic dimension and it is assumed that EO will determine the extent of EM practices which will eventually affect firm growth. Design/methodology/approach: A survey was used as a research instrument and was applied to the owner managers of small Turkish enterprises. Data were collected from 221 independently owned and operated small manufacturing firms that employ less than 150 employees in Istanbul. Findings: Results confirm also that in this study EO affects firm growth. The explanatory power of our model increases when EO is accompanied by EM. Therefore, it can be concluded that EO achieves better results when it is supported by the appropriate management activities. Implications: For researchers, the application of these scales in a different setting has important implications. The factor analysis results showed that some factors were eliminated. The risk taking dimension of EO revealed negative results with growth. Therefore, some dimensions of these concepts have to be defined in accordance with culture. Originality/value: There is limited knowledge about the relationship between EO, EM and firm growth. This paper examines the interaction between EO and EM and provides evidence on their combined impact on small firm growth. © Emerald Group Publishing Limited.
Keywords: Business development; Entrepreneurialism; Small firms; Turkey